2000
DOI: 10.1097/00001199-200012000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Improvement/Rehabilitation of Memory Functioning with Neurotherapy/QEEG Biofeedback

Abstract: This article presents a new approach to the remediation of memory deficits by studying the electrophysiological functioning involved in memory and applying biofeedback techniques. A Quantitative EEG (QEEG) activation database was obtained with 59 right-handed subjects during two auditory memory tasks (prose passages and word lists). Memory performance was correlated with the QEEG variables. Clinical cases were administered the same QEEG activation study to determine their deviations from the values that predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 22 publications
4
36
0
Order By: Relevance
“…Neurofeedback therapy can be used for a wide range of neurologic and psychiatric problems [3][4][5][6][7][8][9][10]. The results of this study suggest that neurofeedback can be used to restore the sympathovagal imbalances, for which wet cupping and reflexological therapies have also been used [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofeedback therapy can be used for a wide range of neurologic and psychiatric problems [3][4][5][6][7][8][9][10]. The results of this study suggest that neurofeedback can be used to restore the sympathovagal imbalances, for which wet cupping and reflexological therapies have also been used [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects of neurofeedback in adults, for example, have been found for Attention Deficit Hyperactivity Disorder [3], traumatic brain injury [4], epilepsy [5], depression [6], migraine [7], addiction [8], anxiety disorders [9] and general cognitive performance [10]. Neurofeedback protocols that aim at inhibiting theta activity while rewarding beta activity have led to successful alleviation of symptoms associated with ADHD, such as deficits in sustained attention, impulsivity and control over hyperactive behaviors (reviews in Butnik, 2005; Fox, Tharp, & Fox, 2005).…”
mentioning
confidence: 99%
“…We are unaware of any research directly addressing whether it is possible for everyone to learn to alter their EEG via neurofeedback. However, research has shown that healthy individuals (Egner & Gruzelier, 2001;Vernon et al, 2003), those suffering brain injury (Thornton, 2000;Tinius & Tinius, 2000), epileptics (Sterman & Macdonald, 1978;Sterman, Macdonald, & Stone, 1974;Uhlmann & Froscher, 2001) and schizophrenics (Gruzelier, Hardman, Wild, & Zaman, 1999) have been able to exhibit changes in their cortical activity following neurofeedback training. (For a comprehensive bibliography see Hammond, 2001b, available in an updated version at www.isnr.org).…”
Section: Journal Of Neurotherapymentioning
confidence: 99%
“…In previous studies using NFT, the focus has been on changes in relative power, and the training electrode placement has usually been set at Cz, C3, or C4. The only publication in which the coherence approach has been reported is that of Thornton (2000). In this study, two brain injured subjects improved by 85% and 168% on an auditory recall task after training to normalize coherence.…”
Section: Journal Of Neurotherapymentioning
confidence: 68%